2021
DOI: 10.1097/adm.0000000000000839
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Early Onset Tranquilizers, Sedatives, and Sleeping Pills Use on Recent Consumption Among Adolescents

Abstract: Background: Adolescents' consumption of tranquilizers, sedatives, and sleeping pills (TSSp) has increased during the last few decades, and TSSp are currently among the substances with the lowest age-ofonset. We characterized current-use patterns of TSSp consumers by age when first taken. Methods: This study used individualized secondary data retrieved from the 2016 Spanish State Survey on Drug Use in Secondary Education (16-18-year-olds), and included all subjects who reported having taken TSSp at any point, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(84 reference statements)
0
2
0
Order By: Relevance
“…However, TSSp&AC is also related to the use of other legal and illicit substances. Moreover, there may be short- and long-term repercussions, such as association with unsafe sex or dangerous driving, violence, and premature death; higher levels of intensive TSSp use in later life [ 15 ]; the exacerbation of the severity and development of concurrent mental disorders; and substance use disorder in adulthood [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, TSSp&AC is also related to the use of other legal and illicit substances. Moreover, there may be short- and long-term repercussions, such as association with unsafe sex or dangerous driving, violence, and premature death; higher levels of intensive TSSp use in later life [ 15 ]; the exacerbation of the severity and development of concurrent mental disorders; and substance use disorder in adulthood [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Public health surveillance data from 2016 show that roughly 1.5 million US adolescents reported tranquilizer/sedative use or misuse in the previous year [ 14 ]. Adolescents’ consumption of TSSps has increased during the last few decades, and TSSps are currently among the substances with the lowest age of onset [ 15 ]. In Spain, previous studies reported that TSSp misuse by adolescents in Spain increased significantly between 2004 and 2014 [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%